GRAFTING A CUCUMBER HYBRID ON PUMPKIN ROOTSTOCKS RESISTANT TO THE PATHOGEN FUSARIUM - Dzhantassov Serik Kazhikhanovich; Shoibekova Alima Zhorabaevna (Academic Journal of Physical and Chemical Sciences, 2021)
Grafting of five varieties of pumpkin on a cucumber hybrid was carried out by the method of notch grafting. As rootstocks used the following varieties of pumpkin: domestic – Aphrodite, Mindalnaya, Karina, Mozoleevskaya 10 and Russian selection – Stofuntovaya and as the scion, a hybrid of cucumber Asylum, recommended for cultivation in protected ground conditions. The research topic is devoted to the study of the influence of pumpkin rootstocks resistant to the Fusarium pathogen on the productivity of the cucumber hybrid in protected ground conditions. Results of studies of the effect of vaccination on various domestic varieties of pumpkin for the growth, development and yield of the hybrid cucumber Asylum showed that when grafting cucumber on pumpkin, the best options compared to the root standard were the varieties of pumpkin Karina and Stofuntovaya.